Investigating the relationship between interoceptive accuracy, interoceptive awareness, and emotional susceptibility - Calì, Giuseppe; Ambrosini, Ettore; Picconi, Laura; Mehling, Wolf; Committeri, Giorgia (Frontiers in Psychology, 2015)
Interoception, the sense of the physiological condition of the body, provides a basis for subjective feelings and emotions. Anterior insular cortex activity represents the state of the body and varies according to personality traits, such as emotional susceptibility (ES) – the tendency to experience feelings of discomfort and vulnerability when facing emotionally-laden stimuli. The accuracy of perceiving one’s own bodily signals, or interoceptive accuracy (IAc), can be assessed with the heartbeat perception task, which is the experimental measure used by most of the existing research on interoception. However, IAc is only one facet of interoception. Interoceptive awareness (IAw) is the conscious perception of sensations from inside the body, such as heart beat, respiration, satiety, and the autonomic nervous system sensations related to emotions, which create the sense of the physiological condition of the body. We developed an Italian version of the recent self-report Multidimensional Assessment of Interoceptive Awareness (MAIA), tested its psychometric properties (reliability, dimensionality, and construct validity), and examined its relationship to ES, as assessed using the Emotional Susceptibility Scale, in a sample (n = 321) of healthy Italian psychology students (293 females, mean age: 20.5 years). In a subgroup of females (n = 135), we measured IAc with the heartbeat perception task. We used a series of correlation/regression analyses to examine the complex interplay between the three constructs. We provide further evidence for a substantial independence of the IAc and IAw measures, confirming previous reports and current theoretical models that differentiate between IAc and IAw. Our analyses elucidate the complex relationship between distinct dimensions of IAw and ES, highlighting the need for continued efforts to shed more light on this topic.